Kajian Laju Infiltrasi Akhir pad DAS Batang Kandih Kota Padang Ditinjau dari Perbedaan Litologi Batuan, Tutupan Lahan,Kadar Air, Porositas Batuan, Konduktivitas Hidrolik Jenuh, Kepadatan, dan Matric Suction - Ermaningsih Ermaningsih; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2018)
Infiltration  flow is quantity of water that enters soil per unit time. This is an important part in hydrology cycle that gives an effect o quantity of water in land. This study is purposed to find out final-filtration speed which is reviewed from differences in rock lithology, land covering, water concentration, rock porosity, saturated hydraulic conductivity, density, and metric suction. This study was conducted in alluvial of Batang Kandih Koto Tangah district Padang city in 15 locations with grid of 1.5 km x 1.5 km.  Study method was used double ring infiltrometer for filtration speed; hand-boring for rock lithology; falling head testing and constant head for saturated hydraulic conductivity; sandcone testing for land density; tensiometer for metric suction; and physical sampling testing in laboratory. Data was analyzed by spatial model and statistical analysis, so that it was resulted in filtration speed distribution model in alluvial of Batang Kandih, and also relationship between water concentration, rock porosity, saturated hydraulic conductivity, density, and metric suction toward number of filtration speed. This study showed that final-filtration speed in alluvial is 0.128 cm/minute; it means that absorption zone is in category of VI/E with very low absorption capability. With statistical modeling, it is obtained that Y = 57.585 X1 + 0.014 X2 + 0.621 X3 – 0.001 X4 + 0.000 X5 + 0.493 with Y = filtration speed, X1 = conductivity, X2 = rock porosity, X3 = density, X4 = water concentration, X5 = metric suction. While R2 is 0.83 means that 0.83 or 83 % of filtration speed score is influenced by these variables and another 17% is influenced by other variables. Water rate of flow that can enter the soil in alluvial is 76,775.58 m3/hour/km2, so that water volume that can enter soil per hour is 76,775.58 m3.Keywords: Infiltration speed, water concentration, land covering, statistical modeling, hydraulic conductivity